Microfluidic Printing of Tunable Hollow Microfibers for Vascular Tissue Engineering. Issue 8 (10th June 2021) - Wu, Zhuhao; Cai, Hongwei; Ao, Zheng; Xu, Junhua; Heaps, Samuel; Guo, Feng
Abstract: Bioprinting of vascular tissues holds great potential in tissue engineering and regenerative medicine. However, challenges remain in fabricating biocompatible and versatile scaffolds for the rapid engineering of vascular tissues and vascularized organs. Here, novel bioink‐enabled microfluidic printing of tunable hollow microfibers is reported for the rapid formation of blood vessels. By compositing biomaterials including sodium alginate, gelatin methacrylate, and glycidyl‐methacrylate silk fibroin, a novel composite bioink with excellent printability and biocompatibility is prepared. This composite bioink can be printed into hollow microfibers with tunable dimensions using a microfluidic co‐axial printing device. After seeding human umbilical vein endothelial cells into the hollow chambers via a microfluidic perfusion device, these cells can adhere to, grow, proliferate, and then cover the internal surface of the printed hollow scaffolds to form vessel‐like tissue structures within 3 days. By combining the unique composite bioink, microfluidic printing of vascular scaffolds, and microfluidic cell seeding and culturing, the strategy can rapidly fabricate vascular‐like tissue structures with high viability and tunable dimensions. The presented method may engineer in vitro vasculatures for the broad applications in basic research and translational medicine including in vitro disease models, tissue microcirculation, and tissue transplantation. Abstract : A novel microfluidic printing method is reported to generate tunable hollow microfibers for vascular engineering. By combining unique composite bioink, microfluidic printing of vascular scaffolds, and microfluidic cell seeding and culturing, our method can fabricate vascular‐like tissue structures within 3 days with high viability and fixability, highlighting the broad applications in vitro disease models, tissue microcirculation, and tissue transplantation.